Design, Synthesis, and Antiproliferative Activity of Novel Indole/1,2,4-Triazole Hybrids as Tubulin Polymerization Inhibitors - Esraa Mahmoud; Dalia Abdelhamid; Anber F. Mohammed; Zainab M. Almarhoon; Stefan Bräse; Bahaa G. M. Youssif; Alaa M. Hayallah; Mohamad Abdel-Aziz (Pharmaceuticals)
Background/Objectives: New indole/1,2,4-triazole hybrids were synthesized and tested for antiproliferative activity against the NCI 60 cell line as tubulin polymerization inhibitors. Methods: All final compounds, 6a–j and 7a–j were evaluated at a single concentration of 10 µM against a panel of sixty cancer cell lines. Results: Compounds 7a–j, featuring the NO-releasing oxime moiety, exhibited superior anticancer activity to their precursor ketones 6a–j across all tested cancer cell lines. Compounds 6h, 7h, 7i, and 7j were chosen for five-dose evaluations against a comprehensive array of 60 human tumor cell lines. The data showed that all tested compounds had significant anticancer activity throughout the nine tumor subpanels studied, with selectivity ratios ranging from 0.52 to 2.29 at the GI50 level. Compounds 7h and 7j showed substantial anticancer effectiveness against most cell lines across nine subpanels, with GI50 values ranging from 1.85 to 5.76 µM and 2.45 to 5.23 µM. Compounds 6h, 7h, 7i, and 7j were assessed for their inhibitory effects on tubulin polymerization. Conclusions: The results showed that compound 7i, an oxime-based derivative, was the most effective at blocking tubulin, with an IC50 value of 3.03 ± 0.11 µM. This was compared to the standard drug CA-4, which had an IC50 value of 8.33 ± 0.29 µM. Additionally, cell cycle analysis and apoptosis assays were performed for compound 7i. Molecular computational investigations have been performed to examine the binding mode of the most effective compounds to the target enzyme.